An analysis of criteria for choosing a first programming language in universities - Прокоп, Юлія Віталіївна; Прокоп, Ю. В.; Прокоп, Юлия Витальевна; Prokop, Yuliia V.; Трофименко, Олена Григорівна; Трофименко, О. Г.; Трофименко, Елена Григорьевна; Trofymenko, Olena H.; Trofimenko, Elena; Северин, Микола Володимирович; Северин, М. В.; Северин, Николай Владимирович; et al. (CEUR-WS, 2019)
The choice of the optimal programming language for teaching students of IT specialties the basics of programming at the universities has been the subject of heated debate over the past decades. It is important to focus on modern and significant criteria while choosing a programming language for the introductory course. After analyzing the arguments put forward by teachers in favor of the use of a particular language, as well as the criteria for choosing a language proposed by researchers, a list of the nineteen most frequently called criteria was compiled. Some regional differences in the approaches to the choice of programming languages and the significance of the criteria have been identified. Considering the specifics of the IT sector in Ukraine, based on the study of literature and authors' experience in teaching the basics of programming, a rating of the criteria for choosing the first language was formed. The rating makes it possible to select an optimal programming language, based on the significance of various criteria, taking into account the specific conditions of a particular university.

Вибір оптимальної мови програмування для навчання студентів ІТ-спеціальностей основам програмування в університетах був предметом гострих дискусій протягом останніх десятиліть. Під час вибору мови програмування для вступного курсу важливо орієнтуватися на сучасні та значущі критерії. Після аналізу наведених викладачами аргументів на користь використання тієї чи іншої мови, а також критеріїв вибору мови, запропонованих дослідниками, було складено список з дев’ятнадцяти найбільш часто називаних критеріїв. Визначено деякі регіональні відмінності у підходах до вибору мов програмування та значущості критеріїв. Враховуючи специфіку ІТ-сфери в Україні, на основі вивчення літератури та досвіду авторів у викладанні основ програмування було сформовано рейтинг критеріїв вибору першої мови. Рейтинг дає можливість вибрати оптимальну мову програмування, виходячи з значущості різних критеріїв, з урахуванням специфіки конкретного університету.
Prokop Y. An analysis of criteria for choosing a first programming language in universities / Y. Prokop, E. Trofimenko, N. Severin, L. Bukata / 42515th International Conference on ICT in Education, Research and Industrial Applications. Integration, Harmonization and Knowledge Transfer // CEUR Workshop Proceedings. Vol. 2387, Volume I: Main Conference, ICTERI 2019; Kherson; Ukraine; CEUR-WS, 12-15 June 2019. - P. 420-425.
Keywords: introductory programming; first programming language; language selection criteria; вступне програмування; перша мова програмування; критерії вибору мови; Research Subject Categories::TECHNOLOGY::Information technology